Argia nataliae n. sp. from Colombia (Odonata: Coenagrionidae) - Garrison, Rosser W. (Zootaxa, 2019)
Argia nataliae n. sp. (Holotype ♂: COLOMBIA, Antioquia Department, Estación Cristalina, about. 28 km west of Puerto Berrio, ca. 6.41 N, 74.58 W, 16 ii 1917, Jesse Hunter & Edward Bruce Williamson leg., in University of Michigan [UMMZ]) is described and illustrated and compared with similar species.